AB0587 Is health-related quality of life of patients with psoriatic arthritis worse than that of patients with psoriasis alone?. (23rd January 2014) - Tezel, N.; Yilmaz, O.; Bodur, H.; Gul, U.; Kulcu Cakmak, S.; Oguz, I. D.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic, progressive, inflammatory arthropathy associated with psoriasis (Ps). PsA can be as destructive as other arthropathies such as rheumatoid arthritis. Both Ps and PsA negatively affect quality of life. The results of the studies that compared the life satisfaction of the patients with Ps and PsA are controversial [1 -3 ]. Objectives: The aim of this study was to compare the health-related quality of life of the Ps patients, the PsA patients and the control subjects. Methods: Eighty patients with PsA (mean age 46±12, %61, 2 woman) according to the CASPAR criteria, fourty patients with Ps (mean age 41±14, %52, 4 woman) and fourty healthy subjects (mean age 42±9, %59, 5 woman) were included in the study. The life satisfaction was evaluated with the Health Assessment Questionnaire for Spondyloarthropathies (HAQ-S) and the Psoriatic Arthritis Quality of Life (PsAQoL) questionnaries. Disease Activity Score 28 (DAS28), Disease Activity index for PSoriatic Arthritis (DAPSA), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score-CRP (ASDAS-CRP) were calculated in order to measure the disease activity in the PsA group. Psoriasis Area Severity Index (PASI) scores of the patient groups were calculated by the same dermatologist. Results: The age and gender distribution were similar among three groups. Ps and PsA groups were also similar regarding PASI scores (mean scores: 4, 7±5 and 3, 5±4, 4 respectively; p>0, 05). Quality of life evaluated with HAQ-S was found worse in the PsA group than in the Ps and control groups. (mean scores: 0, 5±0, 5 0, 2±0, 5 0, 1±0, 3 respectively; p PsA-Ps <0, 05, p PsA-control <0, 05 p Ps-control>0, 05). Quality of life evaluated with PsAQoL was found worse in the PsA and Ps groups than in the control group but same in the PsA and Ps groups (mean scores: 6, 9±5, 4; 7±5, 9; 3, 3±4, 2 respectively; p PsA-Ps >0, 05, p PsA-control <0, 05, p Ps-control <0, 05). Disease activity indices were all significantly high in the PsA group than in the Ps and the control groups. Both HAQ-S and PsAQoL were found significantly moderate-weak correlated with disease activity indices (DAS28, DAPSA, BASDAI, ASDAS-CRP). Conclusions: It was found that the patients with Ps and PsA had worse life quality than the healthy individuals. Quality of life was found related with the disease activity for the patients with PsA. As PsAQoL is composed of questions that predominantly examine the psychological condition, it is recommended to use HAQ-S along with PsAQoL while evaluating health-related quality of life of patients with PsA. References: Rosen CF, Mussani F, Chandran V, Eder L, Thavaneswaran A, Gladman DD. Patients with psoriatic arthritis have worse quality of life than those with psoriasis alone. Rheumatology (Oxford). 2012 Mar;51(3):571-6. Rüschenschmidt C, Somberg B, Häussler G, Lohmann J. Comparison of patients with psoriasis vulgaris vs. psoriatic arthritis with regard to the reported quality of life. Rehabilitation (Stuttg). 2008 Dec;47(6):343-9. Prinz JC, Fitzgerald O, Boggs RI, Foehl J, Robertson D, Pedersen R, Molta CT, Freundlich B. Combination of skin, joint and quality of life outcomes with etanercept in psoriasis and psoriatic arthritis in the PRESTA trial. J Eur Acad Dermatol Venereol. 2011 May;25(5):559-64. Disclosure of Interest: None Declared